The Embracing Digital Banking: An Innovation Acceptance Model Perspective in Indonesian Islamic Banks - M. Fauzan; Andri Soemitra; Marliyah (Yayasan Darussalam Bengkulu, 2026)
Background: This study investigates the determinants of users’ behavioral intention to adopt Islamic digital banking in Indonesia through the lens of the Innovation Acceptance Model (IAM). The purpose of this research is to identify which factors business support, perceived trust, perceived ease of use, perceived usefulness, attitude, perceived behavioral control, and perceived economic considerations significantly influence adoption intention Method: A mixed-methods design was employed, combining Structural Equation Modeling Partial Least Squares (SEM-PLS) to assess demand-side perceptions with Analytic Network Process (ANP) to prioritize supply-side strategies for Islamic banks Results: The findings reveal that business support, trust, ease of use, usefulness, attitude, and behavioral control positively and significantly shape behavioral intention, while the economic factor does not exert a significant effect. This suggests that in the context of Islamic finance, trust, Sharia compliance, security, and convenience outweigh financial considerations in driving adoption. The results also highlight the pivotal role of institutional support and digital literacy in shaping favorable perceptions, especially among student and young adult users who formed the majority of the sample. Conclusion: The novelty of this research lies in applying IAM to Islamic digital banking, demonstrating that not all theoretical constructs universally apply, thereby offering opportunities for contextual refinement of the model. Practically, the study emphasizes the need for Islamic banks to enhance support services, ensure visible Sharia compliance, simplify user experiences, and strengthen trust mechanisms. Overall, this research contributes to both theory and practice by broadening the understanding of digital banking adoption within a faith-based financial system. findings, implications, and the novelty of the study